Magnetic resonance imaging biomarkers of gastrointestinal motor function and fluid distribution - Khalaf, Asseel; Hoad, Caroline; Spiller, Robin C.; Gowland, Penny A.; Moran, Gordon W.; Marciani, Luca (Baishideng Publishing Group Inc, 2015)
Magnetic resonance imaging (MRI) is a well established technique that has revolutionized diagnostic radiology. Until recently, the impact that MRI has had in the assessment of gastrointestinal motor function and bowel fluid distribution in health and in disease has been more limited, despite the novel insights that MRI can provide along the entire gastrointestinal tract. MRI biomarkers include intestinal motility indices, small bowel water content and whole gut transit time. The present review discusses new developments and applications of MRI in the upper gastrointestinal tract, the small bowel and the colon reported in the literature in the last 5 years.